Diversity of Phytoplankton Communities in a Tropical River Basin, Nigeria - Moruff, Adelakun Kehinde; Mu’azu, Mu’azu Mohammed; Patric, Amali Rosemary; Lawrence, Omotayo Olabode (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Biological assessment is a useful alternative for understanding the ecological quality of aquatic ecosystems because biological communities integrate the environmental effects of water. This work investigates the diversity and abundance of phytoplankton in the Upper Jebba Basin of the Niger River in Nigeria. We sampled phytoplanktons by dragging plankton nets at three stations from March to May 2015 for qualitative and quantitative samples. Qualitative plankton samples were collected by towing 55μm mesh hydrobios plankton nets just below the water surface for five minutes at each sampling station. Quantitative samples, on the other hand, were collected by filtering 100 litres of water fetched with a bucket through a 55μm mesh hydrobios net. Both samples were preserved separately in a 4% buffered formalin solution. A total of 3160 cells/ml of phytoplanktons from taxa were identified in the study. High dominance of Oscillatoria sp., Microcystis sp., Chlorella sp., Pediastrum sp. and Synendra indicate that this lake has high amount of organic waste, polluted predominantly by upstream concerns (i.e., mining, agricultural, and domestic) and should be monitored strictly by relevant agencies in order to additional reduced health hazards caused by these pollutants.HYDRO Nepal JournalJournal of Water, Energy and EnvironmentIssue: 19Page: 52-56